The selective isolation of novel cDNAs encoded by the regions surrounding the human interleukin 4 and 5 genes. - Morgan, J G (1992)
We have developed modifications to direct cDNA selection that allow the rapid and reproducible isolation of low abundance cDNAs encoded by large genomic clones. Biotinylated, cloned genomic DNAs are hybridized in solution with amplifiable cDNAs. The genomic clones and attached cDNAs are captured on streptavidin coated magnetic beads, the cDNAs are eluted and amplified. We have applied this protocol to a 425kb YAC that contains the human IL4 and IL5 genes. After two cycles of enrichment twenty-four cDNAs were evaluated, all of which were homologous to the YAC. DNA sequencing revealed that nine cDNAs were 100% homologous to the interferon regulatory factor 1 (IRF1) gene. Six clones were 70% homologous to the murine P600 gene, which is coexpressed with IL4 and IL5 in mouse Th2 cells. The nine remaining clones were unique within the sequence databases and were non redundant. All of the selected cDNAs were initially present at very low abundance and were enriched by as much as 100,000-fold in two cycles of enrichment. This modified selection technique should be readily applicable to the isolation of many candidate disease loci as well as the derivation of detailed transcription maps across large genomic regions.